Emerging priorities and concerns in the wake of the COVID-19 pandemic: qualitative and quantitative findings from a United States national survey - Schwartz, Carolyn E.; Borowiec, Katrina; Waldman, Ariel H.; Sutherland, Tai; Contreras, Briana; Abatan, Elizabeth; Huang, I-Chan; Rohde, Gudrun; Rapkin, Bruce D.; Skolasky, Richard L. (Frontiers in Public Health, 2024)
Ethics approval. The protocol was reviewed and approved by the WCG Independent Review Board (#2021164).All participants provided informed consent prior to beginning the survey.All participants agreed to their data being published in a journal article.Availability of data and material. The study data are confidential and thus not able to be shared./Competing interest. All authors declare that they have no potential conflicts of interest and report no disclosures. Further, none of the author institutions are related to government or other political actors, and there are no other interests or interest groups connected with these organizations. Funding. C.E. Schwartz, K. Borowiec, and A. Waldman received research support from DeltaQuest Foundation. IRB amendment costs were funded by contributions from IC Huang and the Faculty of